2022
DOI: 10.1002/adma.202207376
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Fouling Zwitterionic Polymeric Colloids as Resuscitation Fluids for Hemorrhagic Shock

Abstract: Colloids, known as volume expanders, have been used as resuscitation fluids for hypovolemic shock for decades, as they increase plasma oncotic pressure and expand intravascular volume. However, recent studies show that commonly used synthetic colloids have adverse interactions with human biological systems. In this work, a low‐fouling amine(N)‐oxide‐based zwitterionic polymer as an alternative volume expander with improved biocompatibility and efficacy is designed. It is demonstrated that the polymer possesses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“… 9 Furthermore, oligomeric N -oxides have the potential to serve as substitutes for other hydrophilic oligomers and polymers, such as polyethylene glycol (PEG). Recent studies revealed that these oligomeric N -oxides have excellent blood compatibility 10 and can be used as stealth reagents for the conjugation to drugs or material surfaces. 11 As many of the underlying principles have only recently been discovered, 12 the number of applications of N -oxides in the healthcare field is currently rapidly growing.…”
Section: Introductionmentioning
confidence: 99%
“… 9 Furthermore, oligomeric N -oxides have the potential to serve as substitutes for other hydrophilic oligomers and polymers, such as polyethylene glycol (PEG). Recent studies revealed that these oligomeric N -oxides have excellent blood compatibility 10 and can be used as stealth reagents for the conjugation to drugs or material surfaces. 11 As many of the underlying principles have only recently been discovered, 12 the number of applications of N -oxides in the healthcare field is currently rapidly growing.…”
Section: Introductionmentioning
confidence: 99%
“…Zwitterionic materials, bearing opposite charges equally distributed at a molecular level, are highly biocompatible due to the superior anti-biofouling properties derived from the strong hydration effect via ionic solvation . They have been widely used as excellent biomaterials in various blood-contacting devices in recent years. ,,, In this work, we installed three types of zwitterionic units, including carboxybetaine methacrylate (CB), sulfobetaine methacrylate (SB), and 2-methacryloyloxyethyl phosphorylcholine (MPC), into the POPs using a one-pot solvothermal free radical polymerization, which is a simple but promising strategy to develop functionalized POPs with remarkable adsorption properties. ,,, The low-cost commercially available divinylbenzene (DVB) was employed to form the rigid porous frameworks that may provide favorable interactions with the aromatic structure of bilirubin. The formed zwitterionic POPs exhibited excellent hemocompatibility and protein-resistant ability and efficient adsorption toward bilirubin in 100% fetal bovine serum (FBS) (Figure ).…”
Section: Introductionmentioning
confidence: 99%